The lens regenerative competency of limbal vs. central regions of mature Xenopus cornea epithelium. (November 2016) - Hamilton, Paul W.; Henry, Jonathan J.
Abstract: The frog, Xenopus laevis, is capable of completely regenerating a lens from the cornea epithelium. Because this ability appears to be limited to the larval stages of Xenopus, virtually all the work to understand the mechanisms regulating this process has been limited to pre-metamorphic tadpoles. It has been reported that the post-metamorphic cornea is competent to regenerate under experimental conditions, despite the fact that the in vivo capacity to regenerate is lost; however, that work didn't examine the regenerative potential of different regions of the cornea. A new model suggests that cornea-lens regeneration in Xenopus may be driven by oligopotent stem cells, and not by transdifferentiation of mature cornea cells. We investigated the regenerative potential of the limbal region in post-metamorphic cornea, where the stem cells of the cornea are thought to reside. Using EdU (5-Ethynyl-2'-deoxyuridine), we identified long-term label retaining cells in the basal cells of peripheral post-metamorphic Xenopus cornea, consistent with slow-cycling stem cells of the limbus that have been described in other vertebrates. Using this data to identify putative stem cells of the limbal region in Xenopus, we tested the regenerative competency of limbal regions and central cornea. These regions showed a similarly high ability for the cells of the basal epithelium to express lens proteins when cultured in proximity to larval retina. Thus, the regenerative competency in the post-metamorphic cornea is not restricted to stem cells of the limbal region, but also occurs in the transit amplifying cells throughout the basal layer of the cornea epithelium.